Hubungan Lingkungan Kerja Dengan Kinerja Guru: di SMA Negeri di Kota Depok, Jawa Barat - Sarah Wulan (LPPM STKIP Kusuma Negara, 2018)
This study aims to determine: relationship between the work environment with performance of teachers The research was conducted on the state senior high school of Depok, West Java. The method used was survey research. The instrument used is questioner. The results of research found that: there is a positive correlation between work environment with performance of teachers. This research concluded that the more condusif of work environment, the performance of teachers is higher.